The relationship between the decrease in Glomerulus Filtration Rate (GFR) and the increase in amount of coronary artery lesions on coronary heart disease patients in Sanglah General Hospital, Denpasar-Indonesia - I Nyoman Triaditya Kresna Putra; I Kadek Susila Dharma; Ida Bagus Rangga Wibhuti (Intisari Sains Medis, 2018)
Coronary heart disease or coronary artery disease is caused by the atherosclerosis process in the coronary blood vessels. The high number of patients with this condition is significantly due to the influence of modern and all instant lifestyle. Among the factors suspected to be capable of influencing the increase in the number of coronary artery lesions in coronary heart patients is the Glomerulus Filtration Rate (GFR). This result is related to the high mortality and morbidity of coronary heart patients. Aim: The purpose of this research is to determine the relationship between the decrease in glomerulus filtration rate (GFR), the disturbance variables (age, gender, hypertension history, diabetes mellitus history, smoking history) and the increase in the number of coronary artery lesions in Sanglah General Hospital. Methods: This research is an analytical observational design with the cross-sectional design using secondary data from the medical records in Sanglah General Hospital Denpasar. This study attains 196 sample. Results: A significant relationship is attained between GFR (<60 ml/ minute) and the increase in the total vessel score (p = 0.017) with an OR 2.47 (CI95% 1.014-6.041). Furthermore, there is a significant relationship between risky age (male >45, female >55) and the increase in total vessel score (p = 0.015) with an OR 3.54 (CI 95% 1.217-10.307). Diabetes mellitus and the increase in the total vessel score also shows a significant relationshipÂ  (p = 0.016) with an OR 2.99 (CI 95% 1.189-7.539). While other risk factors such as gender, hypertension, and smoking have an insignificant relationship (p > 0.05). In the multivariate analysis, GFR (<60 ml/ minute) is a predictor of the vessel score (p=0,050) with an adjusted value of OR 1.86 (CI 95% 0.735-4.725). There are some other variables in which are significant predictors of the increase in vessel score. Risky age (male >45, female >55) (p=0,048) with an adjusted OR value of 3.08 (CI 95% 1.012- 9.407) and also diabetes mellitus (p=0.044) with an adjusted OR value of 2.65 (CI 95% 0.145-0.973) are those predictors. Conclusion: Hence, it appears that GFR (<60 ml/ minute), risky age (male >45, female >55) and diabetes mellitus have a significant relationship with the increase in vessel score and are predictors of the increase in vessel score. While gender, hypertension, and smoking do not have significant relationships with the increase in the amount of vessel score.